The effect of skill exercises enhanced by visual responses in learning football scoring skills for female students - Abbas Dhiab, Adil (International Journal of Psychosocial Rehabilitation, 2020)
Skill training is the basis for students to learn skills for all events and sports and not only for futsal football, if practiced in an orderly manner on the basis of correct scientific bases and is specifically prepared to conform to the type of motor duty required of the student to perform or do and promotes visual feedback to provide information on performance or skill to be learned or corrective information. The problem of research lies in the weakness of these two skills in the second-grade middle students, so the researcher prepared skilled exercises enhanced by feedback to address this problem, and the goal of the research is to identify the effect of skill exercises enhanced by visual feedback in learning my skills Handling and scoring football lounges for middle school students, while the research community is represented by 531 female students for the second middle grade of the average martyr Iman, the sample was 02 students from Division A (experimental) and 02 students from Division B.